THE SOCIAL EXCLUSION AS A PROBLEM OF SELF-REALIZATION OF THE ELDERLY - Olesya Koropetska (Vasyl Stefanyk Precarpathian National University, 2015)
The article presents the problem of social exclusion, which in the context of such challenges of global society as poverty, inequality, migration, aging of population, has become one of the most urgent in different countries and continents. It is actual both, for the residents of the USA and for the citizens of Ukraine. While living in different countries, we are the residents of our common "house"- Earth and many problems of modern global world make us more close to each other than we even can think. Among them - a problem of social exclusion and aging of population, which destroyes the democratic and human rights both of the inhabitants of Appalachians and the hutsuls, living in Carpathian Mountains in Ukraine. The social, cultural and behavioral aspects of the problem of exclusion and aging of population are analyzed in the article. Peculiarities of aging, cognitive and emotional state of personalities in the period of aging, the personality's attitude towards aging and social exclusion reflect the feelings and experience of people and show that they are similar as for residents of Appalachian region and for gutsuls of Carpathian mountains. In the article it is stressed that social exclusion is dangerous for people of all ages, especially for people from families, for residents of mountain regions, for orphans and disabled. Not having sufficient capacity to manage the situation, they all feel powerless and unable to manage their life. That is why most countries of the world pay great attention to overcome social exclusion. And since the second half of the 90-th the fight with social exclusion is an integral part not only of the EU's and of the USA's social policy, but it also has become an important direction of the social work in Ukraine.